Molecular Diagnosis of Tuberculosis - Nurwidya, Fariz (Chonnam Med J, 2018)
Tuberculosis (TB) is one of the leading causes of adult death in the Asia-Pacific Region, including Indonesia. As an infectious disease caused by Mycobacterium tuberculosis (MTB), TB remains a major public health issue especially in developing nations due to the lack of adequate diagnostic testing facilities. Diagnosis of TB has entered an era of molecular detection that provides faster and more cost-effective methods to diagnose and confirm drug resistance in TB cases, meanwhile, diagnosis by conventional culture systems requires several weeks. New advances in the molecular detection of TB, including the faster and simpler nucleic acid amplification test (NAAT) and whole-genome sequencing (WGS), have resulted in a shorter time for diagnosis and, therefore, faster TB treatments. In this review, we explored the current findings on molecular diagnosis of TB and drug-resistant TB to see how this advancement could be integrated into public health systems in order to control TB.